From the ocean to our kitchen table: anthropogenic particles in the edible tissue of U.S. West Coast seafood species - Traylor, Summer D.; Granek, Elise F.; Duncan, Marilyn; Brander, Susanne M. (Frontiers in Toxicology, 2024)
Microplastics (MPs) and other anthropogenic particles (APs) are pervasive environmental contaminants found throughout marine and aquatic environments. We quantified APs in the edible tissue of black rockfish, lingcod, Chinook salmon, Pacific herring, Pacific lamprey, and pink shrimp, comparing AP burdens across trophic levels and between vessel-retrieved and retail-purchased individuals. Edible tissue was digested and analyzed under a microscope, and a subset of suspected APs was identified using spectroscopy (μFTIR). Anthropogenic particles were found in 180 of 182 individuals. Finfish contained 0.02–1.08 AP/g of muscle tissue. In pink shrimp (Pandalus jordani), the average AP/g was 10.68 for vessel-retrieved and 7.63 for retail-purchased samples; however, APs/g of tissue were higher in retail-purchased lingcod than vessel-retrieved lingcod, signaling possible added contamination during processing from ocean to market. Riverine young adult Pacific lamprey contained higher concentrations of APs (1 AP/g ±0.59) than ocean phase adults (0.60 AP/g ±0.80 and p = 0.08). Particle types identified were 82% fibers, 17% fragments, and 0.66% films. These findings suggest a need for further research into technologies and strategies to reduce microfiber pollution entering the environment.